2013
DOI: 10.1177/1477153512471520
|View full text |Cite
|
Sign up to set email alerts
|

Subjective preferences and colour quality metrics of LED light sources

Abstract: To understand people's judgement of the naturalness of object colours and preference for the lit environment, lighting booth experiments were conducted. Seven different LED spectral power distributions, all at correlated colour temperatures of 2700 K, 4000 K and 6500 K, were simulated for high CIE colour rendering index (Ra), high colour quality scale (CQS) colour preference scale (Qp) keeping Ra ¼ 80, high feeling of contrast index (FCI) keeping Ra ¼ 80, high CQS relative gamut area scale (Qg) keeping Ra ¼ 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…Another technique uses more than three different colored LEDs (red, green, blue) to produce white light [35]. Increasing the component color will result in better spectral and color rendering properties.…”
Section: Technology Of Led Lampsmentioning
confidence: 99%
“…Another technique uses more than three different colored LEDs (red, green, blue) to produce white light [35]. Increasing the component color will result in better spectral and color rendering properties.…”
Section: Technology Of Led Lampsmentioning
confidence: 99%
“…Therefore, more potential colour expressions can be reflected from materials in the environment. Generally, if the CRI value of a light source is > 80, the light source is suitable for indoor lighting . Therefore, it may be regarded as a potential candidate for a red‐emitting phosphor in converting blue LED light.…”
Section: Resultsmentioning
confidence: 99%
“…their chromaticity coordinates lie above the black body curve. Theoretically, this transmitted light will not be preferred by the user, as Dangol et al [31] and Islam et al [32] found that the observer preferred LED SPDs (spectral power distribution) with D uv values of the light sources were either negative or close to the black body locus. D uv values of light sources affect subjective preference.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, from the studies [31][32][33][34], it was clear that R9 is not an indicator of subjective preference. However, the chroma and colourfulness values of object colours calculated using CAM02-UCS have a great influence on the subjective preferences, especially for the naturalness and colourfulness (subjective measure).…”
Section: Discussionmentioning
confidence: 99%